The Problem of Natural Evil: Dao’s In-naturation and Christ’s Incarnation - Cha, Jaeseung (Journal of reformed theology, 2025)
While Daoism offers valuable insights into ecotheology, particularly in its view that nature possesses inherent dignity and serves all beings, its lack of a comprehensive account of natural evil poses a challenge to fully addressing ecological issues. Similarly, the theology of ‘deep incarnation’—which posits that Christ became flesh as a complex unity of biological components within the process of evolution—faces a difficulty in adequately engaging with the problem of natural evil. However, the sacramental work of Christ in restoring creation, alongside our active participation in this restoration, offers a potential framework for reconstructing Christian ecotheology.